2018
DOI: 10.3389/fmicb.2018.00112
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Survey of Viral and Bacterial Causes of Childhood Diarrhea in Khartoum State, Sudan

Abstract: Diarrheal disease is a major public health problem for children in developing countries. Knowledge of etiology that causes diarrheal illness is essential to implement public health measures to prevent and control this disease. Published studies regarding the situation of childhood diarrhea in Sudan is scanty. This study aims to investigate viral and bacterial etiology and related clinical and epidemiological factors in children with acute diarrhea in Khartoum State, Sudan. A total of 437 fecal samples were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 18 publications
2
16
0
1
Order By: Relevance
“…The high prevalence of single Adenovirus infection, only next to rotavirus, in our study tallies with the GEMS re-analysis study where, when assessed with PCR-based methods, Adenovirus incidence was five times more than previously reported using microbiological methods [17,22], shifting this enteropathogen to become among the top six diarrhoea attributable pathogens [23,24]. However, our study did not find attributable cases of moderate-to-severe diarrhoea due to Adenovirus.…”
Section: Discussionsupporting
confidence: 73%
“…The high prevalence of single Adenovirus infection, only next to rotavirus, in our study tallies with the GEMS re-analysis study where, when assessed with PCR-based methods, Adenovirus incidence was five times more than previously reported using microbiological methods [17,22], shifting this enteropathogen to become among the top six diarrhoea attributable pathogens [23,24]. However, our study did not find attributable cases of moderate-to-severe diarrhoea due to Adenovirus.…”
Section: Discussionsupporting
confidence: 73%
“…Secondly, we explored the differences of alpha and beta diversity of intestinal microbiota from NSCLC patients in response to osimertinib therapy. In previous study, Zhuang et al (2019) found that there was no significant reduction in alpha diversity of intestinal microbiota in lung cancer patients compared to healthy individuals. In line with it, our results indicated that there were almost no significant differences in richness, phylogenetic diversity, and Shannon diversity between NSCLC patients and healthy individuals (P > 0.05, Supplementary Table S4).…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, no significant difference was observed in the richness and Shannon diversity of intestinal microbiota in NSCLC patients between pre-therapy (T1) and post-therapy (T2, T3, T4, T5, T6, T7, T8, T9, T10) ( P > 0.05, Supplementary Table S4 ), indicating that osimertinib therapy did not play great roles in alpha diversity of intestinal microbiota. However, we found that there was significantly different in beta diversity between pre-therapy and post-therapy in NSCLC patients based on the dissimilar test ( P < 0.05, Supplementary Table S5 ), suggesting that osimertinib therapy has made the intestinal microbial community composition changed from the whole ( Zhuang et al, 2019 ). At the same time, there was a little separation among NSCLC samples with different treatment cycles, and between healthy individuals and NSCLC patients ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations